(untitled) (Journal of Plant Disease Sciences, 2022)
Sweet Orange (Citrus sinensis L Osbeck), is India’s most important fruit crop and plays an important role in the country’s fruit economy. Dry root rot caused by Fusarium solani, experiencing significant production constraints as caused significant yield loss. In vitro efficacy of seven broad spectrum fungicides were evaluated and found fungi static against Fusarium solani. Significant reduction in the mycelial growth of Fusarium solani was observed in treatment Carbendazim 12% + Mancozeb 63% WP and Carbendazim 50% WP. While fungicide Cymoxanil 8% + Mancozeb 64% WP was found least effective. However, the growth of isolate Fs-7 was found statistically superior over rest of the isolates. Among the bio-agents tested, significant reduction in the mycelial growth and highest mycelial growth inhibition of Fusarium solani was observed in the treatment Trichoderma harzianum.